Insight into geochemistry of basaltic rocks from Mt Cameroon and characterization of the mantle source - Ngounouno Yamgouot, Fadimatou; Bertrand Gbambie Mbowou, Isaac; Ngounouno, IsmaÃ¯la; Abdoul Youpoungam, Azizi; Daama, Isaac; DÃ©ruelle, Bernard (International Journal of Advanced Geosciences, 2018)
Alkaline volcanic activities occurred in the Mt Cameroon at the ocean-continent boundary of the Cameroon Line. It is characterized by a volcanic association of alkali basalts and hawaiites extruded during the late Miocene to Recent times. The major and trace element geochemistry of the Mt Cameroon are consistent with the fractional crystallization of olivine Â± clinopyroxene Â± plagioclase (Â± amphibole). Petrographical and mineralogical study reveals the presence of xenocryts (olivine, clinopyroxene and spinel) in Mt Cameroon basalts. Their composition are similar to xenoliths and rocks crystals and they come from cumulates formed in the upper lithospheric mantle. Mt Cameroon magmas were generated near the boundary of garnet and spinel mantle stability domains (60â€“75 km depth), at the base of the lithospheric mantle that the compositions of the Mt Cameroon magmas are consistent with derivation from a infralithospheric mantle that was metasomatised by carbonatite melts. Basaltic volcanism in the Mt Cameroon occurred probably as a result of minor plume activity coupled with lithospheric extension.Â Â